The Board of Directors and The Performance of Companies on Conducting Merger in Indonesia - Rahmawati, Setia Dwi Ratna; Pertiwi, Medi Septa Ayu (El-Barka, 2021)
This study aims to examine the impact on the result of the merger which causes the adjustment structure of the board of directors toward the changes in the performance of companies that conducting mergers in Indonesia. Company performance seen as the dependent variable will be evaluated from the accounting performance and market performance. Accounting performance is measured by Return on Assets (ROA) and market performance is measured by Tobin's Q. The independent variable in this study is Board Size (the size of the board of directors) which measured by looking at the number of boards of directors in the company. The sources of data and its types that utilized for the study are company secondary data. The data includes companies that carried out mergers in 2005-2008 and the analysis period obtained after 10 years the companies merged in 2005-2018. The sampling method used in this study was purposive sampling. This study uses a total sample of 8 non-financial companies listed on the Indonesia Stock Exchange (BEI) with a total sample of 79 observations. The result of this study shows that changes in the size of the board of directors have significant impact on changes in Return on Assets (ROA) and changes in Tobin's Q.